Conselhos gestores de unidades de conservação : espaços de aprendizagem através da participação social - Marques, Ketulyn Füster (2018)
This dissertation aims to analyze the learning processes that occur during social participation in two management councils of protection areas in the Rio Grande do Sul state. The option for a space of social participation demonstrates the consonance of this paper with theories that approach learning as a product of social practice, considering in a dialogical way aspects of the subjects, the environment and the historical-cultural context in which they are developed. The Activity Theory, which originated the studies of Lev S. Vigotski and has developments to the current days, with emphasis on the contributions of Alexie Nikolaevich Leontiev and Yrjö Engeströn, support the theorical discussion of this work. The perspective of Jean Lave and Ettiene Wenger on learning situated in communities of practice and the formulations proposed by the anthropologist Tim Ingold, which leads to thinking the learning processes from the subject's perspective as "being-in-the-world", also provide reflections about the proposed theme. As a methodological strategy, was developed a research with a qualiquantitative approach, with the case study as the base. From the perspective of motivation to become a counselor, considering that the reason, according to Leontiev, designates that in which the necessity becomes objective in the conditions considered and for which the activity is oriented, the observations evidenced the presence of three distinct groups: counselors who already present in their trajectory involvement with ecological issues and aim mainly at the creation of the protection area, the surrounding community and residents of the area, who had changes in their way of cultural reproduction and for which the council works as an approximation space and negotiation with management, and people who keep an economical link with the implementation of the unit, whose motivations are related to its effectiveness activities. Beyond the specific objectives of each group, the participation of the different subjects converges to a fundamental immediate objective, to become a counselor. The representativeness was a very prominent aspect in the speeches of the participants of the research, since the identification of the counselor with the group can attribute greater legitimacy. The affirmation of the identity requires on the part of the counselors tolerance and empathy with the different opinions and realities that emerge in the councils, and all the interviewees attached great importance to coexistence with differences as a form of learning. The conclusion points that the learning in the councils of the protected areas that are opportunized through the established relationships, be it in the previous and external experiences to the councils, that contribute to the formation of the identity and motivation of the counselors, as well as the exchanges and tensions that are established within the context of these collegiate, through the interlacement between different actors (with different motivations and world views), the context in which they are located and the way in which the nature converges to integrate in this context.